Implementasi Nilai Ukhuwah Islamiyyah dan Sikap Tasamuh pada Komunitas NU dan MD di Desa Ngembalrejo, Bae, Kudus - Ida Rahmawati; Intan Rahmalina; Siti Karomatun Nadziroh; Ahmad Fatah (Yayasan Literasi Sains Indonesia, 2025)
This study examines the implementation of the values of ukhuwah Islamiyyah (Islamic brotherhood) and tasamuh (tolerance) within the NU (Nahdlatul Ulama) and MD (Muhammadiyah) communities in Ngembalrejo Village, Bae, Kudus. The objective is to understand how these two Islamic organizations practice these values to foster social harmony amidst differences in religious views and traditions. The research employs a qualitative approach with field research, collecting data through in-depth interviews with NU and MD members, as well as documentation. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the NU and MD communities in Ngembalrejo Village successfully build harmony through mutual respect, communal cooperation (gotong royong), and fostering social connections (silaturahmi). Despite differences in religious practices, such as qunut and tahlilan, both communities maintain harmony by prioritizing the values of ukhuwah Islamiyyah and tasamuh. Supporting factors, including collaboration in social activities and awareness of the importance of unity, play a crucial role in strengthening intercommunity relations. This study demonstrates that Islamic values can serve as a foundation for creating harmonious coexistence amid diversity.